Financial Liberalization and Banking Risks in the Waemu Zone: Do Fintechs Matter? - Yao Séraphin, PRAO (International Journal of Accounting and Financial Reporting, 2024)
This study aims to examine the role of fintech development in the relationship between financial liberalization and banking risks in WAEMU countries. To do this, we used macroeconomic data from WAEMU countries, except of Guinea Bissau, due to lack of data, over the period 2011-2021. Methodologically, we use the PCSE (Panel-Corrected Standard Error) method of Beck and Katz (1995). The results revealed that fintechs amplify the banking risk reduction effect of financial liberalization. In terms of economic policy implications, the study suggests that the authorities should step up the process of financial liberalization and pay particular attention to adequate regulation of fintechs.